INTEGRATING MANGAYUN SONG LYRICS AS A REPRESENTATION OF SOUTH TAPANULI LOCAL WISDOM IN DEVELOPING LITERARY APPRECIATION TEACHING MATERIALS FOR GRADE XI STUDENTS - Khoiriah Hasanah Nasution; Lili Herawati Parapat; Khatib Lubis; Nikmah Sari Hasibuan; Eli Marlina Harahap (FORUM PAEDAGOGIK, 2026)
Literary appreciation instruction in Grade XI requires contextual teaching materials and operational assessments so that students can interpret texts, analyze intrinsic elements, and formulate evidence-based conclusions regarding theme and moral message. This study aims to map local wisdom values in Mangayun lyrics and to develop literary appreciation teaching materials based on these lyrics in the form of an e-module equipped with staged LKPD and an assessment rubric, as well as to examine its feasibility in terms of validity, readability, practicality, and effectiveness. The study employed an R&D approach using the 4D model (define, design, develop, disseminate) at SMA Al-Ahliyah Aek Badak, involving 35 Grade XI students as field-test participants and one collaborating teacher. Content analysis of 38 lines identified 45 occurrences of values, dominated by family affection (15; 33.33%), religiosity (11; 24.44%), togetherness/community (9; 20.00%), aesthetics/metaphor (5; 11.11%), gratitude (3; 6.67%), and almsgiving/sharing (2; 4.44%). Product validity assessed by five validators across 30 items yielded Aiken’s V values of 0.65-0.95, with a mean of 0.81. Student readability reached a mean of 84.15%, student practicality 85.85%, and teacher practicality 95%. Effectiveness indicated an increase in scores from a pretest mean of 65.17 (SD = 5.89) to a posttest mean of 85.94 (SD = 5.27), representing a gain of 20.77 points. The findings confirm that the Mangayun-lyrics-based literary appreciation e-module is feasible and effective for strengthening evidence-based literary appreciation while integrating local wisdom into instruction.